Thermodynamic evolution of secluded vector dark matter: conventional WIMPs and nonconventional WIMPs - Kwei-Chou Yang (Journal of High Energy Physics, 2019)
Abstract The secluded dark matter resides within a hidden sector and self-annihilates into lighter mediators which subsequently decay to the Standard Model (SM) particles. Depending on the coupling strength of the mediator to the SM, the hidden sector can be kinetically decoupled from the SM bath when the temperature drops below the mediator’s mass, and the dark matter annihilation cross section at freeze-out is thus possible to be boosted above the conventional value of weak interacting massive particles. We present a comprehensive study on thermodynamic evolution of the hidden sector from the first principle, using the simplest secluded vector dark matter model. Motivated by the observation of Galactic center gamma-ray excess, we take two mass sets ∼ O $$ \mathcal{O} $$ (80 GeV) for the dark matter and mediator as examples to illustrate the thermodynamics. The coupled Boltzmann moment equations for number densities and temperature evolutions of the hidden sector are numerically solved. The formalism can be easily extended to a general secluded dark matter model. We show that a long-lived mediator can result in a boosted dark matter annihilation cross section to account for the relic abundance. We further show the parameter space which provides a good fit to the Galactic center excess data and is compatible with the current bounds and LUX-ZEPLIN projected sensitivity. We find that the future observations of dwarf spheroidal galaxies offer promising reach to probe the most relic allowed parameter space relevant to the boosted dark matter annihilation cross section.